Cumplimiento del Protocolo de Bioseguridad de atención Odontológica. Universidad Nacional de Chimborazo, 2018 - Sánchez Izurieta, Cecilia Lizeth (2019)
The biosafety protocols are standards that must be met with responsibility in each of the procedures, to prevent and reduce accidents associated with work practice and to avoid the transmission of infectious diseases. The present investigation was carried out with the objective of analyzing compliance with the application of the biosafety protocols in the dental care of the students of the Dental Care Unit of the National University of Chimborazo in the period October 2018-March 2019, through a mixed qualitative and quantitative observational, cross-sectional descriptive study, with a sample of 120 students of Integral Clinic I, II, III and IV, through a questionnaire validated by construct, developed by the authors of the Colombian Journal of Dental Research and the checklist prepared as part of the Hospital Biosecurity Manual ¨Dr. Salvador Allende¨ from Chile. The information obtained was codified and analyzed in the database in the statistical program SPSS v.25. clinics is deficient. The majority of students possess a basic level of knowledge about biosafety, biological risks and infectious-contagious diseases that can be acquired during clinical practice; there is a high percentage that do not know about the protocol to follow during work accidents with biological factors; it was possible to demonstrate that there is no difference in the application of biosafety processes between each clinic, that is to say that the level of management of biosafety (60%) in the